Berardinelli-Seip congenital lipodystrophy in a 5-year-old girl. - Rakesh, Y.R.; Vishalakshi, S. Pandit (European Journal of Pediatric Dermatology, 2023)
Berardinelli-Seip congenital lipodystrophy (BSCL) is a rare autosomal recessive disorder characterized by generalized lipoatrophy, acanthosis nigricans, diabetes mellitus, and hypertriglyceridemia. Aggressive control of diabetes is necessary and challenging in these patients due to the associated severe insulin resistance. We report a case of 5-year-old girl who presented with acromegaloid facies, acanthosis nigricans and diabetes mellitus in consideration of its rarity.